Effects of exogenous amylolytic or fibrolytic enzymes inclusion on in vitro fermentation of lactating dairy cow diets in a dual-flow continuous-culture system - J.R. Vinyard; A. Ravelo; E. Sarmikasoglou; H.F. Monteiro; J.A. Arce-Cordero; M.L. Johnson; B.C. Agustinho; R.R. Lobo; M.G. Yungmann; A.H.R. Winter; L.M. Gilbertsen; M.N. Mills; et al. (Journal of Dairy Science, 2023)
ABSTRACT: The objective of this study was to determine the effects of including exogenous amylolytic or fibrolytic enzymes in a diet for high-producing dairy cows on in vitro ruminal fermentation. Eight dual-flow continuous-culture fermentors were used in a replicated 4 × 4 Latin square. The treatments were control (CON), a xylanase and glucanase mixture (T1), an α-amylase mixture (T2), or a xylanase, glucanase, and α-amylase mixture (T3). Treatments were included at a rate of 0.008% of diet dry matter (DM) for T1 and T2 and at 0.02% for T3. All treatments replaced the equivalent amount of soybean meal in the diet compared with CON. All diets were balanced to have the same nutrient composition [30.2% neutral detergent fiber (NDF), 16.1% crude protein (CP), and 30% starch; DM basis], and fermentors were fed 106 g/d divided into 2 feedings. At each feeding, T2 was pipetted into the respective fermentor and an equivalent amount of deionized water was added to each fermentor to eliminate potential variation. Experimental periods were 10 d (7 d for adaptation and 3 d for sample collection). Composite samples of daily effluent were collected and analyzed for volatile fatty acids (VFA), NH3-N, and lactate concentrations, degradability of DM, organic matter, NDF, CP, and starch, and flow and metabolism of N. Samples of fermentor contents were collected from each fermentor at 0, 1, 2, 4, 6, and 8 h after feeding to determine kinetics of pH, NH3-N, lactate, and VFA concentrations over time. All data were analyzed using PROC GLIMMIX of SAS (SAS Institute Inc.), and the repeated variable of time was included for kinetics measurements. Treatment did not affect mean pH, degradability, N flow and metabolism, or the concentrations of VFA, NH3-N, or lactate in the effluent samples. Treatment did not affect pH, acetate:propionate ratio, or the concentrations of lactate, NH3-N, total VFA, acetate, propionate, butyrate, isobutyrate, valerate, or caproate. However, the concentration of total VFA tended to change at each time point depending upon the treatment, and T2 tended to have a greater proportion of 2-methylbutyrate and isovalerate than CON, T1, or T3. As 2-methylbutyrate and isovalerate are branched-chain VFA that are synthesized from branched-chain amino acids, T2 may have an increased fermentation of branched-chain amino acids or decreased uptake by fibrolytic microorganisms. Although we did not observe changes in N metabolism due to the enzymes, there could be changes in microbial populations that utilize branched-chain VFA. Overall, the tested enzymes did not improve in vitro ruminal fermentation in the diet of high-producing dairy cows.